Actual challenges, risks and security safety - Forca, Božidar (Array, 2020)
Security is one of the most common terms in the modern world. This statement is supported by the fact that the term security is used in a wide range of areas. The subject of this paper is national security and the challenges, risks and threats to that security in contemporary international relations. The purpose of the work is twofold. First, to show the diversity of theoretical understanding of the term challenge, risk and threat by various authors. On the other hand, the overriding goal is to analyze the relationship to the challenges, risks and threats in different countries. When it comes to national security, challenges, risks and threats, most often, are identified in a document called the national security strategy. This document, as one of the highest in the hierarchy of political acts of every state, when it comes to security, is passed by almost all modern states of the world. The analysis of numerous national security strategies has revealed that it is possible to identify: 1) the challenges, risks and threats that appear in all strategies, 2) the challenges, risks and threats of security that appear in most strategies, and 3) the challenges, risks and threats of security which are country specific.